300 years of hydrological records and societal responses to droughts and floods on the Pacific coast of Central America - Guevara Murua, Alvaro; Williams, Caroline A.; Hendy, Erica J.; Imbach, Pablo (Copernicus GmbH, 2018)
The management of hydrological extremes and impacts on society is inadequately understood because of the combination of short-term hydrological records, an equally short-term assessment of societal responses and the complex multi-directional relationships between the two over longer timescales. Rainfall seasonality and inter-annual variability on the Pacific coast of Central America is high due to the passage of the Inter Tropical Convergence Zone (ITCZ) and the El Niño–Southern Oscillation (ENSO). Here we reconstruct hydrological variability and demonstrate the potential for assessing societal impacts by drawing on documentary sources from the cities of Santiago de Guatemala (now Antigua Guatemala) and Guatemala de la Asunción (now Guatemala City) over the period from 1640 to 1945. City and municipal council meetings provide a rich source of information dating back to the beginning of Spanish colonisation in the 16th century. We use almost continuous sources from 1640 AD onwards, including > 190 volumes of Actas de Cabildo and Actas Municipales (minutes of meetings of the city and municipal councils) held by the Archivo Histórico de la Municipalidad de Antigua Guatemala (AHMAG) and the Archivo General de Centro América (AGCA) in Guatemala City. For this 305-year period (with the exception of a total of 11 years during which the books were either missing or damaged), information relating to Catholic rogation ceremonies and reports of flooding events and crop shortages were used to classify the annual rainy season (May to October) on a five-point scale from very wet to very dry. In total, 12 years of very wet conditions, 25 years of wetter than usual conditions, 34 years of drier conditions and 21 years of very dry conditions were recorded. An extended drier period from the 1640s to the 1740s was identified and two shorter periods (the 1820s and the 1840s) were dominated by dry conditions. Wetter conditions dominated the 1760s–1810s and possibly record more persistent La Niña conditions that are typically associated with higher precipitation over the Pacific coast of Central America. The 1640s–1740s dry period coincides with the Little Ice Age and the associated southward displacement of the ITCZ.